Multifocal Intestinal Extranodal Marginal Zone Lymphoma Presenting With Autoimmune Hemolytic Anemia: A Case Report - Ali Emre Bardak; Naci Senkal; Kanan Nuriyev; Alpay Medetalibeyoglu (Annals of Internal Medicine: Clinical Cases)
Extranodal marginal zone lymphoma of the intestine is a rare, indolent non-Hodgkin lymphoma that often presents with nonspecific symptoms, making diagnosis challenging. We report a 74-year-old woman who presented with severe anemia attributable to autoimmune hemolytic anemia. Imaging revealed splenomegaly and intestinal wall thickening, whereas subsequent endoscopy showed ulcerated lesions in the ileocecal valve, transverse colon, and descending colon. Biopsy results confirmed extranodal marginal zone lymphoma. Treatment with the R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) regimen led to partial remission of the lymphoma and complete resolution of autoimmune hemolytic anemia.